Poly(4-Methyl-1-Pentene) Mixed-Matrix Membrane Fabrication With Silica Nanoparticle Filler For Co2 N2 Gas Separation Application - Subramaniam, Reasmyraj R (Universiti Sains Malaysia, 2022)
Carbon dioxide (CO2) separation from flue gas with the use of membrane technology has become the focus of researchers over the past decades due to its lower energy consumption and cheaper alternative. In this thesis, mixed matrix membrane (MMM) of poly(4-methyl-1-pentene) (PMP) with silica nanoparticles was studied to determine the feasibility of using MMM to separate CO2 from nitrogen (N2) gas. Viscosity of solution with various PMP wt.% was measured to find the critical concentration of polymer. To confirm that, a full dense PMP membrane with various PMP wt.% was fabricated at room temperature and tested using various feed pressure to determine the effect of pressure and polymer concentration on dense layer of the membrane. Water contact angle and FTIR-ATR was used to characterize the fabricated PMP membrane and MMM membrane. The water contact angle of both membrane surface without modification such as plasma treatment or coating that have been obtained ranged between 111⁰ and 114⁰ which makes the membrane to be classified as hydrophobic membrane. The SEM image on the surface of pristine PMP membrane showed no significant difference between various PMP concentrations. The SEM images on the cross section of the pristine PMP membrane showed that when PMP wt.% increases, the thickness of the pristine PMP increases as well. The trendline of gas permeance of CO2 and N2 as well as the selectivity does not differ greatly with feed pressure. 7 wt.% PMP fabricated at room temperature seems to be the best condition to fabricate MMM based on the gas permeance test. The CO2 and N2 permeance is 3.51 ± 0.15 GPU and 0.29 ± 0.02 GPU respectively, and with CO2/N2 selectivity as 12.04 ± 0.26. The parameter was then used to fabricate MMM with varying filler loading. The CO2 permeance and the N2 permeance increased as well as the CO2/N2 selectivity increased compared to pristine PMP. SEM imaging is used to observe the effect of silica nanoparticles concentration on the thickness of MMM and the agglomerations as well. When filler concentration (wt.%) increases, the thickness of membranes were almost similar but the agglomerations increase. With 7.5 wt.% silica loading at 1 bar, the MMM seems to give the best gas permeance performance. The permeance of CO2 is 13.88 ± 0.45 GPU and the permeance of N2 is 0.59 ± 0.01 GPU which makes the highest ideal selectivity to be 23.34 ± 0.34 with less deviation. In our research, we conclude that MMM is more suitable compared to pristine PMP for CO2/N2 gas separation application.